VAGINAL AGENESIS ARZOBISPO LOAYZA HOSPITAL LIMA-PERU - Alcántara Ascón, René (2015)
12 patients with vaginal agenesis, treated between April 7970 to March 1988, with the purpose of presenting its incidence, management and complications were studied. One case per 3,311 hospitalizations was found. Vaginal agenesis the sole finding had 4 women in the other 8 were also rudimentary uterus (3 cases), uterine agenesis (2 cases), testicular feminization (1 case), bilateral renal PROSIS (1 case) and ureteral bifidity (1 case). Vaginasplastía techniques were Wharton (5 cases) and Mc Indoe (3 cases). There was no complications in 3 patients, while the remaining 5 had vaginal stenosis, vaginal infection (1 case), hemorrhage (1 case), urinary tract infection (1 case) and incision of the pouch of Douglas (1 case). 4 women underwent reintervention with vaginal narrowing with satisfactory outcome.